In children and adolescents with temporomandibular disorder assembled with juvenile idiopathic arthritis - no association were found between pain and TMJ deformities using CBCT - J. Fischer; T. A. Augdal; O. Angenete; E. G. Gil; M. S. Skeie; A. N. Åstrøm; K. Tylleskär; K. Rosendahl; X.-Q. Shi; A. Rosén; The NorJIA (Norwegian JIA Study - Imaging, oral health, and quality of life in children with juvenile idiopathic arthritis) (BMC, 2021)
Abstract Background Children and adolescents with juvenile idiopathic arthritis (JIA) may suffer from temporomandibular disorder (TMD). Due to this, imaging diagnosis is crucial in JIA with non-symptomatic TM joint (TMJ) involvement. The aim of the study was to examine the association between clinical TMD signs/symptoms and cone-beam computed tomography (CBCT) findings of TMJ structural deformities in children and adolescents with JIA. Methods This cross-sectional study is part of a longitudinal prospective multi-centre study performed from 2015-2020, including 228 children and adolescents aged 4-16 years diagnosed with JIA, according to the International League of Associations for Rheumatology (ILAR). For this sub-study, we included the Bergen cohort of 72 patients (32 female, median age 13.1 years, median duration of JIA 4.5 years). Clinical TMD signs/symptoms were registered as pain on palpation, pain on jaw movement, and combined pain of those two. The severity of TMJ deformity was classified as sound (no deformity), mild, or moderate/severe according to the radiographic findings of CBCT. Results Of 72 patients, 21 (29.2%) had pain on palpation at and around the lateral pole, while 41 (56.9%) had TMJ pain upon jaw movement and 26 (36.1%) had pain from both. Of 141 TMJs, 18.4% had mild and 14.2% had moderate/severe structural deformities visible on CBCT. CBCT findings were not significantly associated with either the pain on palpation or the pain on jaw movement. A significant difference was found between structural deformities in CBCT and the combined pain outcome (pain at both palpation and movement) for both TMJs for the persistent oligoarticular subtype (p = 0.031). Conclusions There was no association between painful TMD and CBCT imaging features of the TMJ in patients with JIA, but the oligoarticular subtype of JIA, there was a significant difference associated with TMJ pain and structural CBCT deformities.